Innate and adaptive immune responses of Arctic charr (Salvelinus alpinus, L.) during infection with Aeromonas salmonicida subsp. achromogenes and the effect of the AsaP1 toxin - Schwenteit, J.M.; Breithaupt, Angele; Teifke, Jens Peter; Koppang, E.O.; Bornscheuer, U.T.; Fischer, Uwe; Gudmundsdottir, B.K. (Fish & Shellfish Immunology, 2013)
Aeromonas salmonicida subsp. achromogenes, the causative agent of atypical furunculosis in many fish species, secretes the toxic metalloendopeptidase AsaP1. This study aimed to analyze innate and adaptive immune parameters induced in Arctic charr (Salvelinus alpinus, L.) infected with wild type (wt) A. salmonicida subsp. achromogenes and its isogenic asaP1 deletion mutant (AsaP1-deficient). Head-kidney, liver and spleen were obtained from i.p. infected charr (wt, AsaP1-deficient), during a time schedule of 7 d post infection. Reverse transcription quantitative real-time PCR (RT-qPCR) was applied to study the expression of immune parameters: pro-inflammatory cytokines IL-1β and TNF-α; anti-inflammatory cytokine IL-10; chemokines CXCL-8 (IL-8) and CC-chemokine; the cytokines IFN-γ and IL-4/13A as tracers for Th1 and Th2 immune responses, respectively; and the cell markers CD8α and CD83. In addition, lymphoid organs were histopathologically examined at days 3 and 7 post infection, including B (IgM) and T (CD3ε) cell staining. The detected immune responses were initially driven by innate mechanisms represented by the up-regulation of pro-inflammatory cytokines and chemokines and later on by adaptive Th2 related responses cumulating in B-cell recruitment as shown by regulation of immune parameters in spleen and head-kidney, with significant differences between mutant and wt infected fish. Histological sections revealed IgM-positive cells around ellipsoid arterioles in spleen, while CD3ε positive cells were found in clusters scattered all over the section. However, histopathological differences were only detected between infected and non-infected fish, but not between AsaP1-deficient mutant and wt infected fish. This work represents the first study on innate and adaptive immune responses of Arctic charr induced by a bacterial infection.